Studies in the comparative anatomy and systematic importance of the hexapod tentorium - Hudson, Gerda Bland (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1954)
During a study of the morphology of the orthopteroid Hexapoda between the years 1939-1941, it appeareded to the writer that further investigation into the structure of the insect tentorium was necessary. The early entomologists laid the foundation or our knowledge or the tentorium but during the latter half of the last century little was added in this particulart field. Comstock and Kochi (1902), as far as the writer is aware are the only workers who have published a paper devoted entirely to the skeleton of the bead of insects, and they did much to clarify both nomenclature and existing knowledge of this structure at that time. Berlese (1909) described a typical tentorlum as observed in orthopteroid Hexapoda and then considered the variations of the tentorium which occur in other groups of insects. Some confusion then appears to have arisen amongst workers, over the origin of the dorsal arms which were erroneously considered by some to be cuticular invaginations and not secondary outgrowths of the anterior tentorial arms. Certain morphologists amongst them, Hoke (1924) Denis (1928), Snodgrass (1928, 1935), Hansen (1930), Walker (1933) Imms (1934), and Symmons (1952), have done much towards improving our knowledge of the tentorium, but all too frequently workers offer brief and inadequate descriptions of this structure in otherwise comprehensive investigations of the insect head. Themain objects in this study are threefold, vlz. (1) The claification of nomenclature (2) The examination and the interpretation ot the tentorium in certain groups of insects. (3) The deliberation as to whether the tentorium is of phylogenetic significance, and thus of use in assessing various schemes of insect classification which have been presented. Introduction, p. 1-2.
Keywords: Insects -- Anatomy